2017
DOI: 10.1007/s40544-017-0178-2
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of stick and slip contact conditions for a coated sphere compressed by a rigid flat

Abstract: Abstract:A finite element analysis is used to study the elastic-plastic contact of a coated sphere compressed by a rigid flat under the stick contact condition. This was done for a wide range of hard coating material properties and coating thicknesses. A comparison with the slip contact condition is presented in terms of the critical contact parameters (at yield inception) and plasticity evolution. Empirical expressions are provided for critical interferences of the first and second yield inceptions, in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…By fixing the elastic modulus and the radius of the substrate, i.e., E su = 200 GPa and R = 10 mm, the model can be determined by four dimensionless parameters: E su /Y su , E co /E su , E co /Y co and t/R. It was shown in [36][37][38] that the dimensionless tribological parameters, such as the critical load and interference, are only related to the above four dimensionless parameters even for different E su and R values. The present dimensionless coating thickness t/R differs from previously used normalization by the radius of contact area e.g.…”
Section: Resultsmentioning
confidence: 99%
“…By fixing the elastic modulus and the radius of the substrate, i.e., E su = 200 GPa and R = 10 mm, the model can be determined by four dimensionless parameters: E su /Y su , E co /E su , E co /Y co and t/R. It was shown in [36][37][38] that the dimensionless tribological parameters, such as the critical load and interference, are only related to the above four dimensionless parameters even for different E su and R values. The present dimensionless coating thickness t/R differs from previously used normalization by the radius of contact area e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The load-interference and interference-contact area relations under the slip contact condition differ from those in Ref. [24] by less than 0.5% and 2%, respectively, and those under the stick contact condition [25] by less than 4% and 5%, respectively.…”
Section: Finite Element Modelmentioning
confidence: 65%
“…Subsequently, they normalized the contact parameters by critical values at the second yield inception and obtained universal dimensionless relations for load-displacement and contact area-displacement in elastic-plastic regime [24]. Ronen et al [25] compared the plasticity evolution and contact parameters under slip and stick conditions and observed that the effect of contact condition was negligible except for a phenomenon occurring close to the contact area.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical methods using the finite element model are applied to the study of stick and sliding contact, [8][9][10] which focus on the initial stage of yielding under full stick, partial slip, and full slip conditions, including the effect of coating. Holmberg 11 studied the stress field, plastic strain, and the pileup for spherical sliding contacts.…”
Section: Introductionmentioning
confidence: 99%